(untitled) (Contemporary Mathematics, 2024)
In this article, we introduce a novel, all-purpose entropy measure and derive a new, all-purpose average codeword length in accordance with it. After that, we determined new average generalized codeword length constraints in terms of additional metrics of generalized entropy. In addition, we demonstrate that the metrics employed in this study are generalizations of other metrics typically employed in the coding and information theory communities.